Chemical characterization and metabolic profiling of Xiao-Er-An-Shen Decoction by UPLC-QTOF/MS - Yang, Ruipei; Wei, Lifang; Wang, Jie; Huang, Shiying; Mo, Pingli; Chen, Qiugu; Zheng, Ping; Chen, Jihang; Zhang, Shangbin; Chen, Jianping (Frontiers in Pharmacology, 2023)
Background: Xiao-Er-An-Shen decoction (XEASD), a TCM formula composed of sixteen Chinese medicinal herbs, has been used to alleviate tic disorders (TD) in clinical practice for many years. However, the chemical basis underlying the therapeutic effects of XEASD in the treatment of TD remains unknown. Purpose: The present study aimed to determine the major chemical components of XEASD and its prototype compounds and metabolites in mice biological samples. Methods: The chemical constituents in XEASD were identified using ultra-high Performance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-TOF-MS/MS). Following this, XEASD was orally administered to mice, and samples of plasma, urine, feces, bile, and tissue were collected in order to identify effective compounds for the prevention or treatment of TD. Result: Of the total 184 compounds identified to be discriminated in the XEASD, comprising 44 flavonoids, 26 phenylpropanoids, 16 coumarins, 16 triterpenoids, 14 amino acids, 13 organic acids, 13 alkaloids, 13 ketones, 10 cyclic enol ether terpenes, 7 citrullines, 3 steroids, and 5 anthraquinones, and others. Furthermore, we summarized 54 prototype components and 78 metabolic products of XEASD, measured with biological samples, by estimating metabolic principal components, with four prototype compounds detected in plasma, 58 prototypes discriminated in urine, and 40 prototypes identified in feces. These results indicate that the Oroxylin A glucuronide from Citri reticulatae pericarpium (CRP) is a major compound with potential therapeutic effects identified in brain, while operating positive effect in inhibiting oxidative stress in vitro. Conclusion: In summary, our work delineates the chemical basis underlying the complexity of XEASD, providing insights into the therapeutic and metabolic pathways for TD. Various types of chemicals were explored in XEASD, including flavonoids, phenylpropanoids, coumarins, organic acids, triterpenoid saponins, and so on. This study can promote the further pharmacokinetic and pharmacological evaluation of XEASD.